Pengaruh Kinerja Public Relations Dan Customer Relations Terhadap Kepuasan Pasien RSUD Dr.Moewardi Di Surakarta - Krismiyati, Titik, Agus Triyono, M.Si (2017)
Purposive in the study was to find to effect of the performance of Public Relations and Customer Relations on Patient satisfaction The Hospital Dr.Moewardi Surakarta. This research uses quantitative researc. To collect data the researchers distributed questionnaires with a sample of 95 Analyss technique uses by multiple linear regression analisys teqnique. Based on the test result optained multiple linear regression constant value of 0.957 with a regressions coeficient of performance of 0.004 Public Relations witch states that there is a sinigficant and positive relationship between the performance of Public Relations to the satisfaction of the customer. While the regression coefficient for the variable generated 0.000 CustomerRelations which states that there is a positive and significant relationship between the Customer Relationship with Patient Satisfaction. For the first-t test produced t arithmatic> ttable with tcount 2.967>1.989 t table for significant value t 0.004<0.05 and then H0 rejected and Ha be accepted. performance Public Relations significant impact on the patient satisfaction te Hospital Dr.Moewardi Surakarta. T test result showed both t arithamtic6.853 > ttable 1.989 to 0.000 t significant value <0.05 so the decision H0 rejected and Ha is accepted then the variable Customer Relations significant influence on patient satisfactions the Hospital Dr.Moewardi Surakarta. T test result showed Fhitung 75.883>Ftable 3.15. This is show that H0 is rejected so the performance of Public Relations and Customer Relations together is such a manner both affect Customer Satisfaction. But as many as 37.7% are influenced by variable onside the research. Keywords : Customer Relations, Hospital, Patient Satisfactions, Performance Public Relation.